Tyres and wheels. Rim profiles and dimensions. Industrial vehicle rims. Specification for rim profiles and dimensions for metric series pneumatic tyres and solid tyres for pneumatic tyre rims Part 4.5.2, (15th July 1996) - British Standards Institution,
No abstract available